The Individual, Work and Organization. Behavioural Studies in Business and Management Students - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1989)
This article reviews the book, "The Individual, Work and Organization. Behavioural Studies in Business and Management Students," by Robin Fincham & Peter S. Rhodes.

Designing Effective Organizations. The Sociotechnical Systems Perspective - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1989)
This article reviews the book, "Designing Effective Organizations. The Sociotechnical Systems Perspective," by William A. Pasmore.

Capitalism vs Socialism? Canadian and Swedish Labour Market Policies Compared - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1989)
This article reviews the book, "Capitalism vs Socialism? Canadian and Swedish Labour Market Policies Compared," by Joseph Smucker & Axel Van Den Berg.

Thriving on Chaos. Handbook for a Managerial Revolution - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1989)
This article reviews the book, "Thriving on Chaos. Handbook for a Managerial Revolution," by Tom Peters.

Managing Technological Development. Strategic and Human Resources Issues - Gattiker, Urs E.; Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1989)
This article reviews the book, "Managing Technological Development. Strategic and Human Resources Issues," by Urs E. Gattiker & Laurie Larwood.